2014
DOI: 10.1038/ismej.2014.8
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater as a point source of antibiotic-resistance genes in the sediment of a freshwater lake

Abstract: Antibiotic-resistance genes (ARGs) are currently discussed as emerging environmental contaminants. Hospital and municipal sewage are important sources of ARGs for the receiving freshwater bodies. We investigated the spatial distribution of different ARGs (sul1, sul2, tet(B), tet(M), tet(W) and qnrA) in freshwater lake sediments in the vicinity of a point source of treated wastewater. ARG contamination of Vidy Bay, Lake Geneva, Switzerland was quantified using real-time PCR and compared with total mercury (THg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
238
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(261 citation statements)
references
References 43 publications
(57 reference statements)
18
238
0
5
Order By: Relevance
“…19,24 Although the abundances of some ARGs in this study were less than previous studies, 27,35 the findings could still demonstrate that the continuous release of residual ARGs and antibiotics from WWTPs effluent could result in the dissemination of ARGs in the downstream environment. 21 Statistical Enrichment of Antibiotic Resistance Genes in RWI Samples. Among all the detected 147 ARGs, a total of 105 unique ARGs were significantly enriched in the RWI samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,24 Although the abundances of some ARGs in this study were less than previous studies, 27,35 the findings could still demonstrate that the continuous release of residual ARGs and antibiotics from WWTPs effluent could result in the dissemination of ARGs in the downstream environment. 21 Statistical Enrichment of Antibiotic Resistance Genes in RWI Samples. Among all the detected 147 ARGs, a total of 105 unique ARGs were significantly enriched in the RWI samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…20,21,37,38 But these approaches have not been amenable to broadspectrum scanning of ARGs in environmental samples. 13 In a recent study on the effect of treated wastewater irrigation on the magnitude of ARGs, six different ARGs (qnrA, tet(O), sulI, sulII, ermB, and ermF) were analyzed using the conventional qPCR method.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was concluded that the bacterial community contributed the most to the ARG changes during sludge bio-drying, followed by MGEs and co-selection from heavy metals. The dominant contribution of bacterial community to the ARGs profile has been proved in various environments (Czekalski et al, 2014;Forsberg et al, 2014;Stepanauskas et al, 2005;Udikovic-Kolic et al, 2014), while this was further elucidated in sludge bio-drying.…”
Section: The Variation Of the Contributors To The Evolution Of Argsmentioning
confidence: 95%
“…Likewise, Gao et al (2012) detected high abundances of the tetO, tetW and sulI genes, as well as residues of tetracycline and sulfonamide in the final effluent from a WWTP in Michigan, USA. The continuous release of ARB, ARGs and antibiotic residues from effluents of WWTPs could cause the dissemination of ARGs in environments receiving these effluents (Czekalski et al, 2014;Wang et al, 2014b;Rodriguez-Mozaz et al, 2015), which has become a global concern (Berendonk et al, 2015). Although reclaimed water has been recognized as an important reservoir of ARB and ARGs (Fahrenfeld et al, 2013), only a limited number of studies have assessed the fate of reclaimed waterderived ARGs in downstream environments (Negreanu et al, 2012;Fahrenfeld et al, 2013), and people are not aware of the potential health risks they are facing.…”
Section: Introductionmentioning
confidence: 99%
“…Although reclaimed water has been recognized as an important reservoir of ARB and ARGs (Fahrenfeld et al, 2013), only a limited number of studies have assessed the fate of reclaimed waterderived ARGs in downstream environments (Negreanu et al, 2012;Fahrenfeld et al, 2013), and people are not aware of the potential health risks they are facing. To date, impacts of treated wastewater on antibiotic resistance have been reported in rivers (LaPara et al, 2011), agricultural soils (McLain andWilliams, 2012;Negreanu et al, 2012;Fahrenfeld et al, 2013;Chen et al, 2014) and sediments (Czekalski et al, 2014), but only a few studies focused on the occurrence and prevalence of ARGs in urban park soils irrigated by reclaimed water (Wang et al, 2014a(Wang et al, , 2014b. Public urban parks play a vital role in the social life of human beings, and provide a potentially important pathway for the spread of ARGs from soil to human pathogens.…”
Section: Introductionmentioning
confidence: 99%